Ergospirometric assessment: Relevance for rehabilitation of stroke subjects. - Polese, Janaine Cunha; Teixeira-Salmela, Luci Fuscaldi; Faria, Luiza Martins; Velloso, Marcelo; Parreira, Verônica Franco (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Cardiorespiratory fitness is markedly reduced in stroke subjects, resulting in patterns of inactivity and sedentary lifestyles. In this sense, tests of aerobic exercises are critical for the prescription of this type of training. Aims: To review the available data regarding the cardiorespiratory, metabolic parameters, and protocols used to assess cardiorespiratory fitness in stroke subjects, and to discuss their relevance for stroke rehabilitation. Method: A literature review was carried out in MEDLINE, CINAHL, EMBASE, and PEDro databases. The articles identified by the initial search strategy were evaluated, according to the following criteria: (1) the target population included stroke subjects, (2) employed a spirometric instrumentation, (3) reported results from randomized clinical trials, experimental, or quasi- experimental designs, and (4) included in the analyses any cardiorespiratory or metabolic parameters to assess cardiorespiratory fitness. Results: The 15 identified studies included a total sample of 665 stroke subjects. The experimental groups received training on cycle ergometers, treadmills, mobility, water, and unilateral lower limb exercises with isokinetic dynamometer. Most studies assessed oxygen consumption, two analyzed anaerobic threshold, and one examined heart rate and respiratory exchange ratios. Conclusions: Although differences between the studies were found regarding the investigated outcomes, the assessment and training protocols, this review found evidence that cardiorespiratory parameters, mainly oxygen consumption, were sensitive to training.